Características de consumo de filgastrim (factor estimulante de colonias de granulocitos) en el servicio de onco-hematología pediátrica del hospital nacional edgardo rebagliati martins- essalud lima, durante el año 2008” - Cenizario Miranda, Ivanner (2009)
This work aims to ascertain the know the characteristics of consumption filgastrim (Colony stimulating factor granulocyte), prescribed in the medical service of pediatric hematology-oncology at the Hospital Edgardo Rebagliati Martins in the year 2008, which was a cross-sectional descriptive study, retrospective drug utilization. We worked with reports from records filgastrim consumption in patients hospitalized in pediatric hematology-oncology HNERM. Of all patients hospitalized in the hematology-oncology patients were treated with 88.31% and 11.69% filgastrim not treated with filgastrim. Regarding the sex of the patients 50.92% were female and 49.08% were male. The increased consumption of filgastrim according to age groups for patients from 0 to 4 years with 43.57%. The most frequent indication was acute lymphoblastic leukemia (C91.0) with 31.22% of total units consumed filgastrim, second malignant tumor was the kidney (C64.X) with 16.54% of total units consumed filgastrim. DDP/100camas-día consumption was expressed as an average of 43.83, the monthly consumption of filgastrim did not show a significant trend to increase or decrease during the study period. The cost of annual consumption was S/. 98 598.03 We conclude that the prevalence of filgastrim was 88.31%, consumption was higher in children under age 5 years, acute lymphocytic leukemia was the diagnosis of increased consumption, the average annual consumption was expressed in DDP/100camas-día 43.83 of the variation in the trend of consumption filgastrim is not a function of time and such variation is not statistically significant during the study period. The annual cost of filgastrim was S/. 98 598.03